Regulation of Dietary Lipid Sources on Tissue Lipid Classes and Mitochondrial Energy Metabolism of Juvenile Swimming Crab, Portunus trituberculatus - Yuan, Ye; Sun, Peng; Jin, Min; Wang, Xuexi; Zhou, Qicun (Frontiers in Physiology, 2019)
An 8-weeks feeding trial with swimming crab, Portunus trituberculatus, was conducted to investigate the effects of different dietary lipid sources on the lipid classes, lipid metabolism and mitochondrial energy metabolism relevant genes expression. Six isonitrogenus and isolipidic experimental diets were formulated to contain fish oil (FO), krill oil (KO), palm oil (PO), rapeseed oil (RO), soybean oil (SO) and linseed oil (LO), respectively. A total of 270 swimming crab juveniles (initial weight 5.43 ± 0.03 g) were randomly divided into six diets with three replications, each consists of 45 juvenile crabs. The results revealed that crabs fed KO had highest lipid content in hepatopancreas and free fatty acids in serum among all diets. The anabolic pathway relevant genes: fas and acc were up-regulated in KO diet. The catabolic pathway relevant genes, hsl, was up-regulated in LO diet, while cpt1 was up-regulated in KO diet. Whereas, the genes involved in the transport and uptake of fatty acids such as fabp1 and fatp4 were down-regulated in crab fed PO and RO diets. Furthermore, the gene expression levels of transcription factors : srebp-1 and hnf4α in KO and SO diets were the highest among all diets. FO and KO diets had significantly higher unsaturation index of mitochondrial membrane than others. The genes related to mitochondrial energy metabolism, such as Atpase6, sirt1 and sirt3 were significantly up-regulated in KO and SO diets. In summary, dietary KO and SO supplementation could improve the lipid metabolism, promote energy production for juvenile swimming crab and improve physiological process and function including molting. These findings could contribute to deepen the understanding of the physiological metabolism of dietary fatty acids for swimming crab.